2021
DOI: 10.1186/s12967-021-03004-z
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2-associated transcription factor 1 Ser290 phosphorylation mediates DNA damage response and regulates radiosensitivity in gastric cancer

Abstract: Background DNA damage response plays critical roles in tumor pathogenesis and radiotherapy resistance. Protein phosphorylation is a critical mechanism in regulation of DNA damage response; however, the key mediators for radiosensitivity in gastric cancer still needs further exploration. Methods A quick label-free phosphoproteomics using high-resolution mass spectrometry and an open search approach was applied to paired tumor and adjacent tissues fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…Similarly, in the latest research, IR induced phosphorylation of serine 290 in BCLAF1 and the co-localization of BCLAF1 with γH2AX, which promoted DDR and radiotherapy resistance of gastric cancer cells ( Fig. 1B-i ) ( 11 ). In addition, Savage et al ( 3 ) discovered that BCLAF1 was identified in the protein interacting with BRCA1, which mediated the formation of the BRCA1-mRNA splice complex after DNA damage, and knockdown of BCLAF1 increased cell sensitivity to IR.…”
Section: Bclaf1 and Rtsupporting
confidence: 55%
See 4 more Smart Citations
“…Similarly, in the latest research, IR induced phosphorylation of serine 290 in BCLAF1 and the co-localization of BCLAF1 with γH2AX, which promoted DDR and radiotherapy resistance of gastric cancer cells ( Fig. 1B-i ) ( 11 ). In addition, Savage et al ( 3 ) discovered that BCLAF1 was identified in the protein interacting with BRCA1, which mediated the formation of the BRCA1-mRNA splice complex after DNA damage, and knockdown of BCLAF1 increased cell sensitivity to IR.…”
Section: Bclaf1 and Rtsupporting
confidence: 55%
“…1A and B-a ). Similarly, a recent study proved that the phosphorylation of BCLAF1 at serine 290 participated in DDR mediated by H2AX phosphorylated on serine 139 (γH2AX) ( 11 ). Lastly, heat shock protein 90α (Hsp90α) was found to bind to BCLAF1 and stabilize its protein structure, thus preventing BCLAF1 from degradation via the ubiquitin-proteasome system (UPS) in HCC ( Fig.…”
Section: Regulation Of Bclaf1 Expression and Functionmentioning
confidence: 94%
See 3 more Smart Citations